Microbiological landscape and parameters of antibiotic resistance of pathogens in patients of neonatal intensive care units - O. I. Butranova; A. A. Gorbacheva; S. K. Zyryanov; O. G. Ni (Фармация и фармакология (Пятигорск))
Neonatal infections remain one of the significant causes of infant mortality in the world. The change in the spectrum of pathogens, as well as their sensitivity to the main antibacterial drugs (ABDs), is a dynamically occurring process, characterized by a gradual increase in the proportion of the most dangerous pathogens, in particular, those belonging to the ESKAPE pathogen group. The study of the structure of pathogens and the parameters of their antibiotic resistance is the main tool for increasing the effectiveness of antibiotic therapy.The aim. To analyze the structure of pathogens of nosocomial infections in patients of neonatal intensive care units (NICU) and assess the parameters of their antibiotic resistance.Materials and methods. A retrospective epidemiological study of data from May 1, 2022 to May 1, 2024 of the laboratory information system LIS-Alice of the Kommunarka Center (Moscow, Russia) and medical documentation of patients with identified growth of microorganisms (MOs) in bacteriological cultures was carried out.Results. The total number of crops was 5179, MOs growth was noted in 39.3% (n=2036) obtained from 734 patients, of which 87.1% were premature. Gram-positive pathogens were found in 59.6%. The top 5 identified MOs were: S. epidermidis (n=386 — 19%), S. haemolyticus (n=264 — 13%), S. aureus (n=218 — 10.7%), K. pneumoniae (n=210 - 10.3%) and E. coli (n=188 — 9.2%). The proportion of MOs belonging to the ESKAPE group was 28.6% (S. aureus — 10.7%; K. pneumoniae — 10.3%; Enterobacter spp. — 3.6%; P. aeruginosa — 2.3%; A. baumannii — 1.1%; E. faecium — 0.5%). Among Staphylococcus spp. — 71.2% were resistant to oxacillin, 53.9% — to gentamicin. At the same time, 100% sensitivity to any of the tested ABDs was not detected. The highest rates of resistance to oxacillin were observed in S. epidermidis (93.8%) and S. haemolyticus (86.7%). Also, 17% of S. aureus strains were resistant to oxacillin. Among K. pneumonia 48.8% were resistant to ceftazidime and 100% to ampicillin; E. coli 28.2% of strains were resistant to ceftazidime, 64.9% to ampicillin, 28.2% to sulfamethoxazole trimethoprim.Conclusion. We found a high frequency of pathogen isolation (with a predominance of gram-positive pathogens) in newborns hospitalized in the ICU (mean gestational age <35 weeks). The results demonstrate alarming trends in relation to MOs resistance parameters and indicate the need for dynamic monitoring of the sensitivity of pathogens to the main ABDs used in the ICU.